The Walasuji Tradition: Forgotten Meanings and Values - Ciptandi, Fajar; Nafi’ah, Ulfah; Akramullah (Journal of Urban Culture Research, 2025)
The Walasuji tradition is one of the cultural activities of the Bugis Makassar community, South Sulawesi, Indonesia. It can be found at wedding celebrations as a large gate made of bamboo called “Baruga” Walasuji. However, it is hard to find Baruga Walasuji at youth’s wedding nowadays. Whereas the tradition has unique meaning and values which are good to preserve. This study employed a data validation triangulation method involving interviews, literature review, and observations. Subsequently, the analysis was carried out using a qualitative approach known as the "Three Layers of Culture" method. The results of the study show how meaning and values of the tradition are transferred to each behaviors of the tradition and how intervention factors affect them. The research shows some behaviors which are not relevant anymore in modern context. Therefore, knowledge about the condition of values and meanings in the Walasuji tradition today can be important information to consider when deciding whether to preserve or innovate so that the tradition survives.